DIGITAL PORTFOLIO OPTIMIZATION IN AGILE PRODUCT DEVELOPMENT ENVIRONMENTS - Damodar Puthiya (IPHO-Journal of Advance Research in Science And Engineering, 2024)
Digital product ecosystems have become increasingly complex as organizations manage multiple interconnected digital initiatives within agile development environments. This study investigates the mechanisms of digital portfolio optimization and examines how strategic prioritization, resource allocation efficiency, agile iteration velocity, market opportunity, technological feasibility, and cross-team dependency complexity influence product delivery performance and overall portfolio outcomes. A quantitative analytical framework was developed to evaluate a portfolio of digital product initiatives using a combination of descriptive statistics, hierarchical clustering, and multiple regression modeling. The results indicate that portfolio prioritization, agile iteration velocity, and resource allocation efficiency significantly enhance product delivery performance, while market opportunity and technological feasibility further strengthen innovation productivity and portfolio return potential. Conversely, excessive cross-team dependency complexity negatively affects development efficiency by introducing coordination challenges within agile workflows. Cluster analysis revealed that high-growth digital portfolios characterized by strong strategic alignment and rapid iteration cycles consistently outperform experimental and maintenance-oriented portfolios across multiple performance indicators. Visualization models further demonstrate that optimal portfolio outcomes emerge when agile execution speed and resource utilization are jointly optimized. Overall, the study highlights the importance of integrating strategic portfolio governance with agile operational practices to achieve sustainable innovation, improved product delivery performance, and long-term digital value creation.